X Zjazd historyków doktryn politycznych i prawnych w Szklarskiej Porębie - Szymański, Łukasz (Czasopismo Prawno-Historyczne, 2018)
X Zjazd historyków doktryn politycznych i prawnych w Szklarskiej Porębie